How income inequality affects the subjective well-being of rural residents? - Guo, Chuyue; Zeng, Fusheng; Xia, Dongping (Frontiers in Public Health, 2025)
Since the initiation of economic reforms and opening-up, China’s economy has achieved remarkable growth, leading to a significant improvement in the standard of living for its people. However, the trickle-down effect of this growth has not been equitably distributed across all segments of society. This study attempts to analyze the subjective well-being (SWB) of Chinese rural residents using data from the 2021 Chinese General Social Survey (CGSS). An ordered probit (OProbit) model is constructed to investigate the impact of income inequality on the subjective well-being of Chinese rural residents. The findings reveal three key insights: (1) the benchmark regression demonstrates a significant negative impact of income inequality on the subjective well-being of Chinese rural residents. (2) Social mentality emerges as a critical mediating channel through which income inequality undermines subjective well-being. (3) The impact of income inequality on subjective well-being varied significantly depending on factors such as age, gender, and marital status. As enhancing well-being gains increasing recognition as a central goal in global public health policy, the findings of this study provide valuable insights for designing policies aimed at improving subjective well-being, particularly in rural contexts.